Reorganization of the Territory of the Silk-Weaving Factory “Red Rose” in Moscow - Kiselev, Sergey (project baikal, 2018)
The article reviews reorganization of the territory of the Silk-Weaving Factory “Red Rose” in Moscow’s Khamovnichesky district. It presents the concept for transformation of an unprofitable Soviet enterprise into a multifunctional business center. It studies the cases that occurred during designing and realization of the project, as well as interaction with investors, clients and partners.